Sequencing-based molecular typing of treponema pallidum strains in the Czech Republic: all identified genotypes are related to the sequence of the SS14 strain - Flasarová, Magdalena; Pospíšilová, Petra; Mikalová, Lenka; Vališová, Zuzana; Dastychová, Eliška; Strnadel, Radim; Kuklová, Ivana; Woznicová, Vladana; Zákoucká, Hana; Šmajs, David (Acta dermato-venereologica, 2012)
A set of 415 clinical samples isolated from 294 patients suspected of having syphilis collected in the Czech Republic between 2004 and 2010 was tested for the presence of treponemal DNA. Standard serological tests showed that 197 patients were syphilis-seropositive and 97 patients were syphilis-seronegative. In each sample, PCR tests for polA (TP0105), tmpC (TP0319), TP0136, TP0548 and 23S rRNA genes were performed. Samples taken from 91 patients were PCR-positive. Molecular typing of treponemal DNA was based on the sequencing of TP0136, TP0548 and 23S rRNA genes. Treponemal DNA was typeable in samples taken from 64 PCR-positive patients and 9 different genotypes were found. The proportion of treponemal strains resistant to macrolide antibiotics was 37.3%. In the DNA samples taken from 39 patients, a parallel treponemal typing approved by Centers for Disease Control and Prevention was performed. The variants of arp and tpr genes appear to combine independently with sequence variants of TP0136, TP0548 and 23S rRNA genes.
Keywords: sekvence nukleotidů; RNA, Ribosomal, 23S; fenotyp; polymerázová řetězová reakce; Male; Phenotype; genetická variace; Genotype; Česká republika; Drug Resistance, Bacterial; Sequence Analysis, DNA; antibakteriální látky; sekvenční analýza DNA; molekulární sekvence - údaje; Adult; dospělí; mužské pohlaví; syfilis; RNA ribozomální 23S; Czech Republic; DNA, Bacterial; DNA bakterií; Treponema pallidum; lidé; ženské pohlaví; Anti-Bacterial Agents; Humans; bakteriální léková rezistence; Ribotyping; Syphilis; genotyp; Molecular Sequence Data; Base Sequence; Polymerase Chain Reaction; Genetic Variation; Female; ribotypizace